2022
DOI: 10.15561/26649837.2022.0403
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of body balance indices according to Body Mass Index categories during physical education lessons for university students

Abstract: Background and Study Purpose. Body stability is an important factor in the manifestation of human motor skills. The purpose of the research is to evaluate the efficiency of balance exercises, applied for 28 weeks, with a frequency of one activity / week, on a group of undergraduate students of the “Dunărea de Jos” University of Galați. Material and Methods. 195 subjects participated (99 males and 96 females), divided for analysis into 3 groups (underweight, N = 21, age = 20.16 ± .38, BMI = 17.46 ± .20); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Our research investigated the link between VMR and BMI. Studies by Raza et al [43], Mocanu et al [44], Parekh et al [45], and Bhat at al. [42] have also examined the association between body mass index and visual-motor responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research investigated the link between VMR and BMI. Studies by Raza et al [43], Mocanu et al [44], Parekh et al [45], and Bhat at al. [42] have also examined the association between body mass index and visual-motor responses.…”
Section: Discussionmentioning
confidence: 99%
“…[42] have also examined the association between body mass index and visual-motor responses. Mocanu et al [44] highlighted that individual with excess weight showed lower average performance than those with normal or low weight. Bhat et al [42] identified a slight positive relationship between BMI and basic visual reaction speed (r=0.17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Category 1 with a small number of participants: the range for men is 42-205 and for women -59-720 [6,13,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It states that it is a systematic planning process based on practical experience and sports science knowledge of structuring (long-term) training according to a training objective and individual level of performance. As a result, the development of the various training programs can be designed as a coaching program, a collective or individual program, over several years or annually, over a long cycle or on a training unit [35,36,37,38]. In addition, the individual training program contains the fundamental guidelines that will allow you to achieve optimal performance.…”
Section: Discussionmentioning
confidence: 99%